Investigating the Impact uf E-Learning as an Alternative for Business Education in Pharmaceutical Industry in Romania by Roi Methodology - Petruţa Blaga; Manuela Rozalia Gabor (Amfiteatru Economic)
The capability of organizations to accumulate and apply new knowledge is a key factor in order to achieve the new competitive standards. A continuous changing diversity, to which the need of adaptation to the changes of external environment is added, speeds up the rate of development and business education. The new information and communication technologies speed up the rate of change and increase the need of education that is subject to a higher information flow. The achievements of information technology, along with changes within society, determine the creation of new paradigms for business education and training. Under these circumstances, e-learning has become one of the main educational forms of human resources in business. This research aims to measure the impact of some initiatives within human resources on an organization, market leader within pharmaceutical field, namely measuring the efficiency of business education programs concerning human resources through e-learning. Under these circumstances, the carried-out research aims to put into practice the theoretical frame of ROI (Return on Investment) methodology of evaluating the business education programs concerning human resources in five stages, suggested by J. J. Phillips. The research validates theoretical data of the surveyed model and it is based on the analysis of the data gathering process within the ROI Methodology. This work shows only aspects related to the measuring of the participants` reaction towards the e-learning business education program, respectively